2020
DOI: 10.3390/socsci9100185
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Fake News Consumption: A Review

Abstract: Combating the spread of fake news remains a difficult problem. For this reason, it is increasingly urgent to understand the phenomenon of fake news. This review aims to see why fake news is widely shared on social media and why some people believe it. The presentation of its structure (from the images chosen, the format of the titles and the language used in the text) can explain the reasons for going viral and what factors are associated with the belief in fake news. We show that fake news explores all possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 119 publications
0
57
1
8
Order By: Relevance
“…This is something that definitely requires further, perhaps qualitative studies and is certain to be one of the aspects that will be investigated in a future extension of this work. One other thing that needs to be mentioned is that in the last decade, the fake news phenomenon has come into force (Baptista and Gradim 2020). Two media that have been flagged as potential sources of fake news are included in the media websites under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This is something that definitely requires further, perhaps qualitative studies and is certain to be one of the aspects that will be investigated in a future extension of this work. One other thing that needs to be mentioned is that in the last decade, the fake news phenomenon has come into force (Baptista and Gradim 2020). Two media that have been flagged as potential sources of fake news are included in the media websites under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The belief and dissemination of fake news seems to be related to psychological, economic and ideological aspects [19,[36][37][38][39][40][41]. Baptista and Gradim (2020b) found that low levels of education or digital literacy, distrust in the media, low cognitive ability, close relationship with other users on social media and people's partisanship or ideological beliefs are the most common factors found in the existing literature [10]. Stories that meet our view of the world (in different aspects such as religious or political issues) are more easily accepted, even if they are wrong [39,42,43].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Online disinformation has become part of the daily life of the reader/user of social media. Through social media, such as Facebook and Twitter, fake news is widely disseminated [5][6][7][8], obtaining, in some cases, greater engagement (that is, shares, reactions and/or comments) than true popular news [4,[9][10][11]. In Portugal, the country where our study is centered, fake news is also a reality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After conducting a systematic research through the main bibliographic reference sources (mainly WOS and Scopus), as well as recent review papers [42][43][44][45], we do not know of any other research papers similar to the analysis proposed here, with content methodology of a representative sample of news items that appeared in the press, in which the researchers themselves contrasted the truth of the news, with the exception of an isolated case taken to the United States sports arena [46]. Therefore, this methodological approach is novel and can be applied to any type of news, not only in the sports field.…”
Section: Methodsmentioning
confidence: 99%